Implementation of the Entrepreneurship Theme to Foster Entrepreneurial Attitudes of Grade IV Elementary School Students - Febryanti, Salsabila Trias; Suhartono, Suhartono; Untari, Esti (Angstrom Centre of Education, 2023)
Entrepreneurship is one of the topics of project strengthening the profile of Pancasila students, which applies at the elementary school level. The school has been given the authority for determining topics that will be enhanced in every class or phase. Throughout the entrepreneurial activities, students’ creativity in entrepreneurship will be expanded furthermore. The purpose of this research is to describe the implementation of the entrepreneurial theme, entrepreneurial attitudes, and obstacles to implementing the entrepreneurial theme at SDN Sawojajar 4 Malang. This research uses a descriptive method and a qualitative approach. Observation, interviews, and documentation obtain the data. The data outcome is approved with the triangles technique. The results show that SDN Sawojajar 4 Malang has been applying the entrepreneurial theme in the Curriculum Merdeka which is adjusted to school environment conditions. The entrepreneurship theme had been carrying by narrating with the P5 teaching module which teachers and effort to develop an entrepreneurial behavior through the innovate lesson.